Manhaj Ta’lim al-Lughoti al-‘Arabbiyati fi al-Madrosati al-Raayati al-Ibtidaiyyah al-Islamiyah ‘ala Dou’i al-Manhaj al-Hukumy Tshalatsata ‘Asyaro (KURTILAS) Dirasat Tahliiliyah Tatbiqiyah - Imroatus Sa’adah; Evi Khulwati (Mauriduna: Journal of Islamic Studies, 2021)
تهدف هذه الدراسة إلى معرفة المنهج الحكومي الثالث عشر (KURTILAS) في تعليم اللغة العربية، ومعرفة منهج تعليم اللغة العربية في مدرسة الراية الإبتدائية الإسلامية، وصف طريقة تطبيق المنهج الحكومي الثالث عشر (KURTILAS) في تعليم اللغة العربية في مدرسة الراية الابتدائية الإسلامية.إنّ اهذه الدراسة تسلك على منهج الوصف التحليلي. وأما الطريقة التي سلكتها الباحثة لإتمام هذا البحث هي طريقة الملاحظة و المقابلة، أما نوع البحث هو بحث مكتبي من حيث إنّ البحث الحالي يعتمد على الكتب في جمع المعلوماته وتحليله، وهو كذلك بحث ميداني من حيث إنّه يقوم بتطبيق الطرق الموضوعة.الخلاصة من نتائج البحث أنّ تعليم اللغة العربية في مدرسة الراية الابتدائية الإسلامية يطبق المنهج الخاص. أنّ الكتاب لمادة اللغة العربية الذي يسخدم في مدرسة الراية الإبتدائية الإسلامية هو كتاب العربية بين يدي أولادنا والموضوعات في هذا الكتاب توافق الموضوعات في مقرّر مادة اللغة العربية في المنهج الحكومي الثالث عشر (KURTILAS) ك(التعرف واألوان والفواكه والأعداد والأيام) .فإذا تعليم اللغة العربية في مدرسة الراية الابتدائية الإسلامية لا يخالف تطبيق المنهج الحكومي الثالث عشر (KURTILAS) بل تزداد جمال تنظيم منهج تعليم اللغة العربية في مدرسة الراية الابتدائية الإسلامية بزيادة المنهج الخاص في هذه المدرسة. The purpous This study is to know the thirteenth government curriculum (KURTILAS) in teaching the Arabic language, and to know the curriculum of teaching Arabic language in Ar-Raayah Islamic Elemntary School, and to describing the method of applying the thirteenth governmental approach (KURTILAS) in teaching the Arabic language in Al-Raya Islamic Primary School.The research methode follows the analytical description method. The method used by the researcher to complete this research is the method of observation and interview. As for the type of research, it is a desk research in that the current research relies on books to collect its information and analysis, and it is also a field research in that it applies the established methods.The conclusion of the research results is that teaching Arabic at Ar-Raayah Islamic Elementary School applies the special curriculum. That the Arabic language book that is used in the Ar-Raya Islamic Elementary School is the Arabic book in “Al-Arabbiyatu bayna yadday aulaadinaa” and the topics in this book correspond to the topics in the Arabic language course in the thirteenth government curriculum (KURTILAS). The thirteenth government curriculum (KURTILAS) like introduction, colors, fruits, numbers, and days), but the beauty of organizing the Arabic language curriculum in Al-Raya Islamic Primary School increases with the increase in the special curriculum in this school.